Difficulties in emotion regulation in treatment-seeking alcoholics with and without co-occurring mood and anxiety disorders. (May 2018) - Bradizza, Clara M.; Brown, Whitney C.; Ruszczyk, Melanie U.; Dermen, Kurt H.; Lucke, Joseph F.; Stasiewicz, Paul R.
Abstract: Emotion regulation difficulties (ERD) are known to underlie mental health conditions including anxiety and depressive disorders and alcohol use disorder (AUD). Although AUD, mood, and anxiety disorders commonly co-occur, no study has examined the association between these disorders and ERD among AUD outpatients. In the current study, emotion regulation (ER) scores of AUD individuals with no co-occurring mental health condition were compared to the ER scores of individuals who met diagnostic criteria for co-occurring mood and/or anxiety disorders. Treatment-seeking AUD individuals ( N  = 77) completed measures of emotion regulation, alcohol use and psychological functioning prior to beginning a 12-week outpatient cognitive-behaviorally oriented alcohol treatment program. Individuals were classified as having no co-occurring mood or anxiety disorder (AUD-0, n  = 24), one co-occurring disorder (AUD-1, n  = 34), or two or more co-occurring disorders (AUD-2, n  = 19). Between-group differences in emotion regulation, quantity/frequency of alcohol consumption, positive and negative affect, affective drinking situations, negative mood regulation expectancies, distress tolerance, alexithymia, trait mindfulness, and psychological symptom severity were examined. Compared with the AUD-0 group, the AUD-2 group reported significantly greater ERD, psychiatric distress and alcohol consumption, more frequent drinking in response to negative affect situations, greater interference from negative emotions, and less use of mindfulness skills. The AUD-1 group differed from AUD-0 group only on the DERS lack of emotional awareness (Aware) subscale. Emotion regulation scores in the AUD-0 group were comparable to those previously reported for general community samples, whereas levels of ERD in the AUD-1 and AUD-2 were similar to those found in other clinical samples. Implications for the inclusion of ER interventions among AUD patients who might most benefit from such an intervention are discussed. Highlights: Participants with two or more comorbid disorders reported significantly greater emotion regulation difficulties. They also reported greater alcohol consumption and drinking in response to negative affect situations. They reported greater psychiatric distress, interference from negative emotions and less use of mindfulness skills.